CONVENTIONALITY CONTROL ON LABOR REFORM (LAW 13.467 / 2017) UNDER THE ANALYSIS OF THE INTER-AMERICAN COURT OF HUMAN RIGHTS JURISPRUDENCE ON ACCESS TO JUSTICE): CONVENTIONALITY CONTROL ON LABOR REFORM (LAW 13.467/2017) UNDER THE ANALYSIS OF THE INTER-AMERICAN COURT OF HUMAN RIGHTS JURISPRUDENCE ON ACCESS TO JUSTICE) (Revista Direitos Humanos e Democracia, 2021)
This current work focuses on the analyze the validity of the legislative changes brought by Law 13.467/2017, called “Labor Reform”, under the sieve of the American Convention on Human Rights (ACHR, 1969) and the international normative provision on the right of access to justice , weighing up the authentic interpretation brought by the evolutionary jurisprudence and consolidated by the Inter-American Court of Human Rights (CorteIDH), advisory and contentious body of the regional protection system created by the Organization of American States (OAS), the Constitution of the Federative Republic of Brazil and the new parameters for granting free justice, attorneys' fees, costs and other procedural expenses, in order to subsidize the application of judicial control of conventionality, as an instrument of double material vertical compatibility, in view of the state obligations to adopt internal human rights. The impacts of legislative changes in guaranteeing unfeasible labor jurisdiction will be examined, through comparison with the precedents of the IACHR and the possibility of recognizing the unconventionality of the devices that confront or restrict access to justice. Through bibliographic and jurisprudential research, based on the deductive method, we seek to trace the dialogue between Labor Rights and Procedural Labor, Constitutional Law and International Human Rights Law, above all, for the purposes of applying conventionality control over domestic law.
Keywords: Labor Reform, Conventional Control, Right of Access to Justice, Human Rights.